Nesticus dimensis new species, a new troglobitic spider from Turkey (Araneae, Nesticidae), with comments on its phylogenetic relationships - Lopez-Pancorbo, Alberto; Kunt, Kadir Boğaç; Blagoev, Gergin; Deltshev, Christo; Ribera, Carles (Zootaxa, 2013)
A new troglobitic spider species, Nesticus dimensis n. sp. (♂ ♀), inhabiting the Dim Cave of Alanya (Antalya Prov., Turkey) is diagnosed and described. The new species belongs to the Eastern Mediterranean Nesticus Group, which includes N. eremita and N. speluncarum as the most common and widespread species along with N. arenstorffi and N. henderickxi. Evolutionary relationships of the taxa belonging to this group of species are discussed on the basis of morphological and molecular data (using cox1, rrnL and H3 gene sequence data).